2021
DOI: 10.1111/jdi.13697
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia in diabetic kidney disease classified by proteinuria and renal dysfunction: A cross‐sectional study from a regional diabetes cohort

Abstract: Aims/Introduction Diabetic kidney disease (DKD) exacerbates dyslipidemia and increases the incidence of atherosclerotic cardiovascular disease. DKD is a concept that includes typical diabetic nephropathy and an atypical phenotype without proteinuria. We investigated dyslipidemia in different DKD phenotypes that have not been fully studied. Materials and Methods Fasting plasma was obtained from 1,073 diabetes patients enrolled in the regional diabetes cohort (ViNA cohort). Non‐proteinuric and proteinuric DKD we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…First, the phenomenon may be modified by the development of renoprotective treatments, such as renin-angiotensin system inhibitors (RASi), lipid-lowering drugs, and sodium glucose cotransporter 2 inhibitors (SGLT2i), which reduce urinary albuminuria. However, RASi was not an independent risk factor for NADKD in multivariate analysis (26), and when excluding users of RASi or lipid-lowering drugs, the prevalence and general characteristics of NADKD resembled those of all patients (12,23,39,48). Second, NADKD may be an early stage of classic DKD.…”
Section: Possible Explanations Of Nonalbuminuric Diabetic Kidney Diseasementioning
confidence: 92%
See 1 more Smart Citation
“…First, the phenomenon may be modified by the development of renoprotective treatments, such as renin-angiotensin system inhibitors (RASi), lipid-lowering drugs, and sodium glucose cotransporter 2 inhibitors (SGLT2i), which reduce urinary albuminuria. However, RASi was not an independent risk factor for NADKD in multivariate analysis (26), and when excluding users of RASi or lipid-lowering drugs, the prevalence and general characteristics of NADKD resembled those of all patients (12,23,39,48). Second, NADKD may be an early stage of classic DKD.…”
Section: Possible Explanations Of Nonalbuminuric Diabetic Kidney Diseasementioning
confidence: 92%
“…Decreased eGFR was defined as eGFR < 60 ml/min/m2. There were 5 studies with inconsistent definitions (2011 Rajiv defined albuminuria as ACR < 220 mg/g; 2019 Masayuki and 2021 Tsutomu defined albuminuria as ACR < 300 mg/g; 2013 Mauro only included patients with GFR < 30 ml/min/m2, and 2016 Ivo defined decreased eGFR as <75 ml/min/m2 (as shown in Table 2) (8,9,30,32,39). After these 5 studies were excluded, 18 studies reported the characteristics of NADKD, and they were included in the meta-analysis (5, 7, 10, 12, 15-18, 22-24, 26, 31, 34-38) (as shown in Additional Table 2).…”
Section: Clinical Characteristics Of Nonalbuminuric Diabetic Kidney D...mentioning
confidence: 99%
“…Interestingly, the lower the eGFR, the greater the dissociation between direct sdLDL-C and Sampson sdLDL-C in patients with diabetes (Table 2). Renal dysfunction associated with diabetes leads to abnormal lipoprotein metabolism, resulting in the development of severe and complex dyslipidemia 14) . This may be an additional explanation for the lower ability to estimate sdLDL-C in patients with diabetes than in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with diabetes (n=1542), including 51 type 1 diabetes, participated in the "ViNA" cohort study aimed to investigate the prognosis of patients with diabetes at Ebina General Hospital 14) . The ViNA cohort study began on October 1, 2019, and the baseline blood samples were collected from October 2019 to December 2021.…”
Section: Methodsmentioning
confidence: 99%
“…Diabetic nephropathy definition under the broad term of Chronic renal(kidney) disease (abbreviated as CKD) is coined as occurrence of renal functions deterioration and the estimated rate (eGFR) of glomerular filtration < 60 ml per min per 1.73 meter square of body surface area, present for a period of 3 months or - ---------------------------------------------------------------------------------------Received on 09-03-2022 Accepted on 17-07-2022 more 14 . In the past few years, elevation of serum triglyceride has been related to onset and progression of nephropathy in diabetics 15 .…”
Section: Introductionmentioning
confidence: 99%